(untitled) (New York, 2000)
This collection of readings presents the state-of-the-art of clinical psychology! Each article, written by an expert in the field, presents the most exciting new developments and coming trends in psychotherapy. The result is a multifaceted preview of psychotherapy in the year 2000 and beyond!
Keywords: Psychotherapy,Change (psychology),Psychotherapy,Psychotherapy; Forecasting,Methods